Management of microcredit in the economic empowerment of women merchants in Huánuco, 2019 - Terrones-Sotomayor, Cesar M. (2020)
The objective of the study was to determine the effect of access to microcredit and the economic empowerment of women merchants in the town of Huánuco, 2019. Methods was a research with a quantitative approach, explanatory level, with a quasi-experimental design only afterwards, with two groups: experimental and control. The sample was made up of 116 women merchants from a food market in the Amarilis district, selected probabilistically at simple random for a known population. An interview guide with general characteristics and access to microcredit and a questionnaire on women's empowerment were applied, previously validated and reliable. Research ethical considerations were applied. The results show differences between the case group that benefited from the microcredit and the control group that did not have such benefit in the ability to: generate economic income and money savings, (Z = -5,506), in the economic support of the business and of individual and family commitments (Z = -5,548); in running the business (Z = -3,480); in sustaining the business and individual and family commitments (Z = -5.548), and to provide economic security to their home (Z = -2.912), the differences being statistically significant (p <0.005). There were no differences in entrepreneurship capacity (Z = -1.608, and p = 0.108). It is concluded that microcredit enables a high level of economic empowerment in 62.1% (36) of the women in the case group; while 96.6% (56) of the control group achieved a medium level of empowerment, these differences being significant (Z = -1.608, and p = 0.001)